Schools as change agents? Education and individual political agency in Uganda. (May 2019) - Datzberger, Simone; Le Mat, Marielle L.J.
Highlights: Uganda's weak democratization process is reflected in the public schooling system. Perceived knowledge of national political institutions is remarkably low. Gender, regional differences and quality of education each affect political agency differently. Women in urban areas indicated lower political agency than men. Abstract: By drawing on the case study of Uganda, we challenge common assumptions about education, gender, regional differences and political agency. Comparing findings from four different regions, we scrutinize whether and how educational institutions empower Ugandan youth to participate in society as active, informed, critical and responsible citizens. Theoretically, we focus on four different aspects of individual political agency that education can foster, namely: understanding of political structures; independent critical thinking; levels of political interest; and political participation. Throughout our analysis, we make use of a survey (N = 497), conducted in 2017 with respondents from secondary schools and universities; and data obtained from 37 qualitative interviews across four regions in Uganda. The aim behind the survey was to move beyond a priori models on how education affects the political agency of individuals. Instead, we offer insights on how Ugandans themselves perceive the politically empowering elements of the education they receive, connecting this to the wider cultural political economy context of Uganda. We find that Ugandan schools make only a very modest contribution towards nurturing an individual's political agency. While the majority of respondents felt they critically reflected on societal issues in school, their knowledge of national political institutions, and on how they would claim and advocate their rights as citizens was remarkably low.